Approaches and impact of non-academic research capacity strengthening training models in sub-Saharan Africa: a systematic review - Mugabo, Lambert (Health Res Policy Syst, 2015)
BACKGROUND: Research is essential to identify and prioritize health needs and to develop appropriate strategies to improve health outcomes. In the last decade, non-academic research capacity strengthening trainings in sub-Saharan Africa, coupled with developing research infrastructure and the provision of individual mentorship support, has been used to build health worker skills. The objectives of this review are to describe different training approaches to research capacity strengthening in sub-Saharan Africa outside academic programs, assess methods used to evaluate research capacity strengthening activities, and learn about the challenges facing research capacity strengthening and the strategies/innovations required to overcome them. METHODOLOGY: The PubMed database was searched using nine search terms and articles were included if 1) they explicitly described research capacity strengthening training activities, including information on program duration, target audience, immediate program outputs and outcomes; 2) all or part of the training program took place in sub-Saharan African countries; 3) the training activities were not a formal academic program; 4) papers were published between 2000 and 2013; and 5) both abstract and full paper were available in English. RESULTS: The search resulted in 495 articles, of which 450 were retained; 14 papers met all inclusion criteria and were included and analysed. In total, 4136 people were trained, of which 2939 were from Africa. Of the 14 included papers, six fell in the category of short-term evaluation period and eight in the long-term evaluation period. Conduct of evaluations and use of evaluation frameworks varied between short and long term models and some trainings were not evaluated. Evaluation methods included tests, surveys, interviews, and systems approach matrix. CONCLUSIONS: Research capacity strengthening activities in sub-Saharan Africa outside of academic settings provide important contributions to developing in-country capacity to participate in and lead research. Institutional support, increased funds, and dedicated time for research activities are critical factors that lead to the development of successful programs. Further, knowledge sharing through scientific articles with sufficient detail is needed to enable replication of successful models in other settings.